Assessment of Demographic Profile and Cytopathological Diagnosis of Thoracic Mass Lesions Using CT-guided FNAC - Darad, Dimple; Chauhan, Savitri (Annals of Pathology and Laboratory Medicine, 2018)
Background and Aim: Computed tomography (CT) guided Fine needle aspiration cytology (FNAC) is a simple, safer, and rapid technique. CT guidance can assist FNAC from any part of thorax without any major complications. FNAC helps distinguish between benign and malignant lesions and also effectively aids in morphological typing of lung cancer, thereby reducing the delay in initiation of specific therapy like chemotherapy or surgery. Materials and Method: Present study was carried out at a department of pathology GMERS Medical College, Gotri, Vadodara, Gujarat. One hundred and twenty three cases of lung mass lesions were evaluated with CT guided FNAC. Smears were stained with May-Grunwald Giemsa and Hemotoxylin & Eosin (H & E) stain for rapid cytopathological evaluation of the lesions. Results: Out of 123 cases included in the study, 90 cases (73.17%) were male and 33 (26.83%) were female. The mean age in malignant cases was 60.3 years whereas it was 50 years in benign lesions. Cytological examination showed that 109 cases were malignant and 14 cases were benign lesions. Cytomorphological diagnosis revealed maximum number of cases belonged to adenocarcinoma (60.9%). Rest of the cases were Squamous cell carcinoma (16.2%), Non-specific inflammation (4.8%), Granulomatous inflammation (3.2%), metastatic deposits (3.2%) and spindle cell neoplasm (1%). Only ten cases could be followed up for histopathological evaluation. All the cases confirmed the primary diagnosis of malignancy on histopathological examination. Conclusion: CT guided FNAC is a simple, and reliable for the diagnosis and sub typing of lung cancer, thereby reducing the delay in initiation of specific therapy like chemotherapy or surgery.